Parasites from land fishes in Great Kwa River, Calabar, Cross River State, Nigeria - Femi O. Bayo; Adebisi Yomi; Alomiri R. Ayo (Advances in Aquaculture and Fisheries Management, 2014)
Parasites of landed fish from the Great Kwa River, Calabar, Cross River State, Nigeria were studied. Parasitological examination of 180 fish samples belonging to 9 taxa from the River showed 50% incidence for Chrysicthys nigrodigitatus, 16.67% for Heterotis noloticus, Clarias gariepinus and Tilapia galileaus respectively and 0% for Hepsetus odoe, Arius gigas, Momyrus rume, Ethmalosa fimbriata and Cynoglossus senegalensis. Parasite infestations were found in the stomach and intestine, and no parasites were found on the fins, skin and gills. Nematodes, cestodes and protozoan were found in decreasing order of abundance. Diphyllobothrium sp. was found in the intestine of C. nigrodigitatus; Camallanus sp. was found in the intestine of H. niloticus and T. galileaus while protozoan cysts were found in the intestine of C. garipinus. Parasites were more prevalent in the fish of 30 to 39.9 cm total length size range. The study determined that in the Great Kwa River the preferred organs of parasites were the intestines and stomach.